2003
DOI: 10.1542/peds.111.3.e255
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific Immunoglobulin E Antibodies in Wheezing Infants: The Risk for Asthma in Later Childhood

Abstract: ABSTRACT. Objective. To evaluate whether the measurement of specific immunoglobulin E (IgE) antibodies to food and/or inhalant allergens in infants who are hospitalized for wheezing can be used to predict later asthma.Methods. Eighty-two children who were hospitalized for wheezing at <2 years of age were followed prospectively until early school age. The baseline data and the characteristics of infancy had been collected at enrollment. At school age, the children were evaluated for asthma and allergic manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 23 publications
(31 reference statements)
3
65
1
4
Order By: Relevance
“…These allergens are known for their potential to cause food hypersensitivities in children and adults.15 Diagnostic utility of serum levels of specific IgE against egg white has been evaluated and it was recommended that a level of 1.3 kU/l corresponding to RAST score 2 or above does not require additional investigations to establish the diagnosis of egg allergy.16 A study investigating wheezing children has shown that RAST test score of 1 and above for specific IgE against egg white is significantly associated with later development of asthma. 17 Although this observation appears to be relevant in context of patients with clinical evidence of allergic disorders the presence of high levels of specific IgE in asymptomatic individuals may also serve as a useful indicator for future development of allergic diseases. In addition, the serum levels of specific IgE antibodies against egg white are believed to be influenced by persistent exposure to the allergen.…”
Section: Discussionmentioning
confidence: 99%
“…These allergens are known for their potential to cause food hypersensitivities in children and adults.15 Diagnostic utility of serum levels of specific IgE against egg white has been evaluated and it was recommended that a level of 1.3 kU/l corresponding to RAST score 2 or above does not require additional investigations to establish the diagnosis of egg allergy.16 A study investigating wheezing children has shown that RAST test score of 1 and above for specific IgE against egg white is significantly associated with later development of asthma. 17 Although this observation appears to be relevant in context of patients with clinical evidence of allergic disorders the presence of high levels of specific IgE in asymptomatic individuals may also serve as a useful indicator for future development of allergic diseases. In addition, the serum levels of specific IgE antibodies against egg white are believed to be influenced by persistent exposure to the allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Phadiatop ® has been widely used as a screening test for respiratory allergies. 5,14,15 In principal Phadiatop ® is an in vitro test that allows individuals who are sensitive to multiple inhalant allergens to be identified simultaneously. In order to be a useful and sensitive method Phadiatop ® must be constituted of the aeroallergens that are most prevalent in the area of study.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The rate of positivity among patients with respiratory allergies was 77.3%, which is comparable to those observed by others. 5,15,21 Another use of a allergy diagnostic test would be its use as a predictive method for later allergic disease development. A number of different researchers studied the positivity of Phadiatop ® as a marker for allergic disease, in particular respiratory ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In children less than two years old hospitalized for wheezing, the presence of R+ for wheat, egg white and domestic dust mites was associated with an increased frequency of asthma later in life. 19 Despite this, specific IgE serum assay is not an available test at the majority of health care services, whether governmental or private. When assessing allergic patients it is important to bear the concept of the allergic march in mind.…”
Section: Controlsmentioning
confidence: 99%